Structure of physical, psycho-physiological development and physical preparedness of children of preschool age. - Kozina Zh.L; Lakhno E.G; Moskalets T.V (Kharkov National Pedagogical University, 2011)
The results of determination of structure of physical development are resulted, psycho-physiological possibilities and physical preparedness of children of age-dependent groups, 1-2, 3-4 and 4-5 years. It is set that development of children from 1 to 5 years takes place getertimely. There is a considerable role of indexes in the initial probed age-dependent period (1-2 years) there is a considerable role of indexes of physical development in development of physical qualities and psycho-physiological possibilities. In age 3-4 the role of level of development of physical qualities and psycho-physiological possibilities increases in the structure of complex preparedness, and in an age-dependent period 4-5 years again there is an increase of role of physical development with the maintain of role of physical preparedness and psycho-physiological possibilities.